2018
DOI: 10.5902/2179460x30650
|View full text |Cite
|
Sign up to set email alerts
|

Estudo do ciclo diário da Camada Limite Planetária durante a estação cChuvosa da Amazônia (GOAmazon 2014/15)

Abstract: In the present study, the evolution the diurnal cycle of planetary boundary layer in the wet season at Amazon region during a period of intense observations carried out in the GOAmazon Project 2014/2015 (Green Ocean Amazon).The analysis includes radiosonde and remote sensing data. In general case, the results of the daily cycle in the wet season indicate a Nocturnal boundary layer with a small oscillation in its depth and with a tardy erosion. The convective boundary layer did not present great depth, respondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…The results showed that the NBL erosion in the region is conditioned by greater energy availability in the early hours of the morning, and how much of H will be used to heat the atmosphere, thus initiating the formation of thermal turbulence. The CBL growth rate after erosion was faster than that observed during the wet season (Carneiro et al 2018). This showed that NBL erosion directly influenced the faster development and maximum height of the CBL.…”
Section: Observational Analysismentioning
confidence: 71%
See 1 more Smart Citation
“…The results showed that the NBL erosion in the region is conditioned by greater energy availability in the early hours of the morning, and how much of H will be used to heat the atmosphere, thus initiating the formation of thermal turbulence. The CBL growth rate after erosion was faster than that observed during the wet season (Carneiro et al 2018). This showed that NBL erosion directly influenced the faster development and maximum height of the CBL.…”
Section: Observational Analysismentioning
confidence: 71%
“…In recent years there has been an increase in PBL studies for several types of biomes, but in the Amazon region, where biosphere-atmosphere interactions are intense and highly complex (Neves and Fisch 2015;Marengo et al 2017;Carneiro et al 2018;Neves et al 2018), the parameters that describe its structure are still little understood.…”
Section: Introductionmentioning
confidence: 99%
“…Sendo um instrumento de alta frequência (com taxa de amostragem de 16 s) é uma ferramenta poderosa para estimar a altura da CLP. de reflexão que estão relacionadas com a umidade (Carneiro, 2018).…”
Section: Ceilometerunclassified
“…Isso indica que a camada limite estável noturna é, em geral, mais baixa que 325 m, sustentando turbulência logo acima, onde as medidas foram tomadas. Esse resultado é consistente com o observado por Carneiro et al (2018) durante o experimento GoAmazon, onde foi concluído que a CLN tem espessura tipicamente da ordem de 300 metros. Há uma pequena variação sazonal, com valores ligeiramente maiores sendo registrados durante a estação chuvosa, o que também era esperado, devido à maior incidência de precipitações convectivas.…”
Section: Caracterização Meteorológica Do Sítio Attounclassified